พุทธวิธีการเรียนการสอน - วรเมธีศรีสกุล, อุทัย; ดีสวนโคก, ชอบ; นางทะราช, อนุสรณ์; เวียงคำ, สิทธิพล; บัวช่วย , สุภาพร; ศรีระวรรณ, สาคร (Journal of Graduate MCU KhonKaen Campus, 2018)
การสอนในทางพระพุทธศาสนามี 3 ลักษณะ คือ แบบร้อยกรอง แบบร้อยแก้ว และแบบร้อยแก้วผสมร้อยกรอง การสอนมี 3 ด้าน คือ พฤติกรรม จิตใจ และปัญญา มีสาระสำคัญ คือ ศีล สมาธิ ปัญญา การสอนของพระพุทธเจ้า มีจุดมุ่งหมาย คือ การสร้างประโยชน์ ความเกื้อกูล และความสุขแก่พหูชน และเกื้อกูลต่อสังคมโลก วิธีการสอนของพระพุทธเจ้านั้นพอสรุปได้ว่ามี 3 ลักษณะคือ 1. สอนแบบร้อยกรอง 2.ร้อยแก้ว 3. สอนแบบร้อยแก้วผสมร้อยกรอง ตัวอย่างคือพระสูตรที่มีคาถาไม่ใช่พุทธวิธีหลักจิตวิทยาและสื่อการสอนของพระพุทธเจ้า อุปกรณ์ที่พระองค์ได้ทรงคิดค้นและทรงนำมาใช้ประกอบการสอนมี 3 วิธี คือ 1. การใช้เหตุการณ์ที่เกิดขึ้นเป็นอุปกรณ์ 2. การใช้ภาพนิมิตเหมือนภาพยนตร์ 3. การใช้วิธีทดลองด้วยตนเองคุณสมบัติของผู้เรียนในพระพุทธศาสนา There are three types of teachings in Buddhism: poem, prose and prose-poem. There are three aspects of the teachings: behavior, mind and wisdom with their essences in precepts, concentration and wisdom instruction. Contributing to the global society, the aim of teaching of the Buddha is to create benefits, comfort and happiness to people. The methods of Buddhist teaching are summarized in three characteristics: 1) teaching by poem; 2) teaching by prose and 3) teaching by poem with prose. An example can be seen in the Sutta with non-Gatha which is not the main Buddhist psychological principles and teaching media of the Buddha. The teaching instruments the Buddha created and suggested are: 1) using the occurred event as the instrument; 2) using the vison as that of the film; 3) using the self-experiment as the qualifications of the learners in Buddhism.